Implemantasi Autentikasi Hotspot Menggunakan Radius Server Mikrotik Router Pada Rumah Sakit Misi Lebak - Gonzaga, Alexander; Putra, Andriyan Dwi (Universitas Amikom Yogyakarta, 2023)
The Lebak misi hospital area currently mostly using wireless networks where usage is increasing and bandwidth is uneven. Between one user and another and the admin only provides password protection for existing access points. which will cause instability between one user and another, therefore the author uses the Radius server as a bandwidth divider as well as security with user authentication and adding a QR code to the authentication. and the author uses the NDLC (Network Development Life Circle) method. As a reference for the radius server configuration using a proxy router. and the results obtained are the percentage of user bandwidth before using the server radius of 0.99Mbps on download and upload of 1.19Mbps for smartphones on laptops of 6.72Mbps for download and upload of 2.21Mbps then after using the radius of the server the average bandwidth speed using user and password of 0.75Mbps for download and 0.80Mbps upload and the success status is very good, all devices can authenticate. and those who can use a QR code of 0.36Mbps for download and 0.44Mbps for Upload with a poor success status because some devices are not compatible for authentication using a QR code by scanning webqr.com.